New Reactivity Involving N-Isothiocyanates: Aminothiocarbonylation and [3+2] Cycloadditions to Form Molecules Containing NNCS Motifs - Ranasinghe Gamage, Indeewari (Université d'Ottawa / University of Ottawa, 2017)
Nitrogen-containing heterocycles are of vital importance for the pharmaceutical and agrochemical industries. The Beauchemin group has been studying rare, amphoteric nitrogen-substituted isocyanates over the past years, and showed that their [3+2] alkene cycloaddition and cascade reactions provide access to a variety of NNCO containing heterocyclic compounds. This triggered interest into the reactivity of the parent N-isothiocyanates, which are also rare, and led to the discovery of aminothiocarbonylation reactions. The products formed are azomethine imines which contain a cyclic -aminothiocarbonyl motif, thus providing a cycloaddition route to these useful dipoles from simple starting materials. Such aminothiocarbonylation reactions were developed with both alkenes and imines as substrates.Apart from cyclic azomethine imine formations, efforts have also been made toward forming the acyclic azomethine imines as intermediates. These intermediates undergo [3+2] cycloaddition to form thiocarbamoyl pyrazolidine derivatives, and a preliminary substrate scope for this new intermolecular reactivity is presented. Other preliminary results include an unexpected Chugaev type reactivity. Collectively, these results show that N-isothiocyanates hold significant potential for the development of new reactivity.
Keywords: aminothiocarbonylation; heterocycles; cycloaddition; isothiocyanates